Pathways from eudaimonic and hedonic motives to life satisfaction via response style - Choi, Damee; Kimura, Motohiro; Kihara, Ken; Akamatsu, Motoyuki; Hosono, Minako; Sugimoto, Fumie; Konishi, Naoki; Fuseda, Kohei; Sato, Toshihisa (Scientific reports, 2025)
Studies have demonstrated an association between eudaimonic and hedonic motives and well-being. However, these studies have not fully quantified the mediating pathways underlying this relationship. This study investigated whether the response style mediates the relationship between these motives and life satisfaction. Japanese individuals ( n = 11,041) participated in this study. We assessed eudaimonic and hedonic motives using the Hedonic and Eudaimonic Motives for Activities–Revised, which includes three subscales: eudaimonic , pleasure , and relaxation . We assessed life satisfaction as a well-being measure using the Satisfaction with Life Scale. The two response styles— facing the fact (corresponding to active coping) and evasion (corresponding to behavioral disengagement)—were evaluated using the Expanded Response Styles Questionnaire. Path analysis was employed to test the mediating effects of response style on the relationship between eudaimonic/hedonic motives and life satisfaction. Results indicated that eudaimonic motive enhanced life satisfaction by increasing facing the fact and reducing evasion. Similarly, pleasure motive increased life satisfaction by promoting facing the fact. In contrast, the relaxation motive reduced life satisfaction by decreasing facing the fact and increasing evasion. These findings suggest that response style is a crucial pathway linking eudaimonic and hedonic motives to life satisfaction.